The Influence of Calcium Chloride Salt Solution on the Transport Properties of Cementitious Materials. (4th June 2015) - Farnam, Yaghoob; Washington, Taylor; Weiss, Jason
Abstract : The chemical interaction between calcium chloride (CaCl2 ) and cementitious binder may alter the transport properties of concrete which are important in predicting the service life of infrastructure elements. This paper presents a series of fluid and gas transport measurements made on cementitious mortars before and after exposure to various solutions with concentrations ranging from 0% to 29.8% CaCl2 by mass. Fluid absorption, oxygen diffusivity, and oxygen permeability were measured on mortar samples prepared using Type I and Type V cements. Three primary factors influence the transport properties of mortar exposed to CaCl2 : (1) changes in the degree of saturation, (2) calcium hydroxide leaching, and (3) formation of chemical reaction products (i.e., Friedel's salt, Kuzel's salt, and calcium oxychloride). It is shown that an increase in the degree of saturation decreases oxygen permeability. At lower concentrations (<~12% CaCl2 at room temperature), the addition of CaCl2 can increase calcium hydroxide leaching, thereby increasing mortar porosity (this is offset by the formation of Friedel's salt and Kuzel's salt that can block the pores). At higher concentrations (>~12%), the formation of chemical reaction products (mainly calcium oxychloride) is a dominant factor decreasing the fluid and gas transport in concrete.